Numerical Simulation of Distribution Characteristics of Hydraulic Fish Habitat Index in 90° Spur Dike Areas - JIANG Li; DENG Xiaolong; ZHONG Liang; CHEN Jingyuan; ZHONG Xueyi; LIU Xiangqian; FU Qiang (Renmin Zhujiang)
The study of fish habitat in spur dike areas is of great significance to the ecological protection of rivers.In this paper,the distribution characteristics of the hydraulic fish habitat index in a spur dike area are discussed by a three-dimensional (3D) mathematical model for water flow.The results reveal that ① the flow velocity increases with the Froude number Fr;the width of the back flow area behind the dike decreases gradually,and the main flow area changes from rapidly varied flow to gradually varied flow and gradually returns to uniform flow.② The flow velocity gradient G in the main flow and back flow areas is small;the areas with G>2 are mainly concentrated on the left and right banks of the water channel and near the spur dike head,and on the cross-section,G declines as Fr grows.③ The distribution characteristics of the kinetic energy gradient M on the section of the spur dike from upstream to downstream are similar to those of G.The high-value areas of M appear on the right bank of the water channel and in the section with the relative channel width B+ of 0.25~0.40 near the spur dike head,but M is small on the left bank of the water channel and has little change along the way.④ With the increase in Fr,the velocity suitability Su in the upstream of the spur dike decreases,while Su at the spur dike and in the downstream cross-section of the spur dike increases.Su of the back flow area in the downstream of the spur dike is small,generally not more than 0.3,while Su in the main flow area may exceed 0.8,which indicates that the spawning habitat of fish in this area is better.The research results can provide a reference for the protection of fish resources in spur dike areas and the construction of ecological waterway projects.